IMPROVEMENT OF FIRM PERFORMANCE AND INTELLECTUAL CAPITAL THROUGH INNOVATION AND COMPETITIVE ADVANTAGE - Siska Maya; Atikah Atikah; Ana Rusmardiana (UNIVERSITAS INDRAPRASTA PGRI, 2021)
Business is undergoing a change called the new wave, which is a change in (traditional) production-based economies into a knowledge-based economy. This is because Intellectual Capital is considered as a source that has a competitive advantage for a company. Information technology (IT) also provides many benefits for companies that use it well. One of the competitive advantages turns out that Intellectual Capital by Small and Medium Enterprises (SMEs) in Indonesia has not been utilized as an asset that can improve company performance. The method used in this study is a quantitative method. The purpose of this study is to explain the influence of Intellectual Capital and IT Competence on Innovation in improving Competitive Advantage and explain the moderating relationship between IT Competence and Knowledge Base View on Firm Performance. Intellectual Capital and IT Competence have no effect on Innovation in improving Competitive Advantage. Innovation serves as a full mediation of intellectual capital with firm performance. Likewise, the competitive advantage functions as a full mediation towards IT Competence and firm performance.